2002
DOI: 10.1007/s004250100645
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxysomal acetoacetyl-CoA thiolase and 3-oxoacyl-CoA thiolase from sunflower cotyledons

Abstract: Following chromatography on hydroxyapatite, the elution profile of the thiolase activity of the glyoxysomal fraction from sunflower (Helianthus annuus L.) cotyledons exhibited two peaks when the enzyme activity was assayed with acetoacetyl-CoA as substrate. Only one of these two activity peaks was detectable when a long-chain thiolase substrate was used in the activity assay. The proteins (thiolase I and thiolase II) underlying the two activity peaks detected with acetoacetyl-CoA were of glyoxysomal origin. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
9
1
2
Order By: Relevance
“…At a concentration of 100 mM imidazole, the recombinant thiolase is also present but is more significantly contaminated with higher and lower molecular weight proteins (Figure 5, lane 6). The size of the AACT purified and characterized from the glyoxysomal fraction of sunflower cotyledons was reported as 63 kDa 13, which is significantly higher than the molecular weight reported here; however, another thiolase activity was reported in that paper and was not further characterized. This second thiolase perhaps corresponds to the thiolase reported here.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…At a concentration of 100 mM imidazole, the recombinant thiolase is also present but is more significantly contaminated with higher and lower molecular weight proteins (Figure 5, lane 6). The size of the AACT purified and characterized from the glyoxysomal fraction of sunflower cotyledons was reported as 63 kDa 13, which is significantly higher than the molecular weight reported here; however, another thiolase activity was reported in that paper and was not further characterized. This second thiolase perhaps corresponds to the thiolase reported here.…”
Section: Resultscontrasting
confidence: 69%
“…Extensive characterization of two thiolase enzymes from the glyoxysomal fraction of sunflower cotyledon tissue has shown that both the Thiolase I and Thiolase II activities occur in this tissue 13. We have previously cloned and purified an enzymatically active 3-ketoacyl CoA thiolase from sunflower cotyledon 14, and here we report the cloning, expression and purification of the acetoacetyl CoA thiolase from the sunflower cotyledon.…”
Section: Introductionmentioning
confidence: 94%
“…It is here that the control of storage fat degradation and channelling of the products towards the biosynthesis of essential compounds such as carbohydrates occurs. [11][12][13][14][15] Peroxisomal KAT is produced in vivo as a precursor carrying a cleavable N-terminal targeting signal. 16,17 The N-terminal segment is not required for activity, nor does it influence the quaternary structure, which is homodimeric in the mature conformation.…”
Section: Introductionmentioning
confidence: 99%
“…En otras especies vegetales como pepino, también se han caracterizado distintas isoenzimas MFP expresadas diferencialmente en distintos tejidos de la planta y con distintas actividades en cada caso (Behrends et al, 1988;Preisig-Muller et al, 1994; Guhnemann-Schafer y Kindl, 1995a;. Por último, las proteínas MFP presentan varias regiones de unión a microtúbulos que le permiten el transporte a través de los mismos, e implica que estas proteínas se encuentren asociadas a microtúbulos además de su localización peroxisomal (Chuong et al, 2002; Kindl, 1993), mango (Bojorquez y Gómez-Lim, 1995), colza (Olesen y Brandt, 1995), cotiledones de calabaza (Kato et al, 1996), girasol (Oeljeklaus et al, 2002) y en Arabidopsis (Hayashi et al, 1998b;Germain et al, 2001). El genoma de Arabidopsis contiene tres genes que codifican proteínas KAT.…”
Section: Componentes De La β-Oxidaciónunclassified
“…En los últimos años, se ha confirmado la presencia de actividad enzimática KAT en varias especies (Olesen et al, 1997;Germain et al, 2001;Oeljeklaus et al, 2002) y ha sido obtenida la estructura cristalina de la enzima de Arabidopsis (Sundaramoorthy et al, 2006).…”
Section: Enzimas Katunclassified